Politics, powers and the environment in Palestine - Qumsiyeh, Mazin B.; Albaradeiya, Issa Musa (Africana Studia, 2022)
The Palestinian environment is suffering from loss of natural resources, neglect of the environment, damage by occupation policies, environmental pollution, low water quality, depletion of water sources, and other human impacts leading to habitat loss and decline in biodiversity. The Israeli occupation makes these issues more and more difficult and continuously adds new challenges to the Palestinian environment. After the Oslo Agreements 1993-1994, the newly established Palestinian National Authority (a supposed state in the making) attempted to deal with the environmental problems. The limited authority given to the Palestinian “authority” does not allow for proper nature protection despite availability of instruments of signed international conventions. We conclude that major achievements in environmental conservation cannot be attained without changing the power dynamics. Yet, smaller scale structural changes such as transparency, environmental awareness, and better alignment of science-policy can and did help the environment. Keywords: Conservation, Biodiversity, colonialism, governance.